2021
DOI: 10.15587/2519-4852.2021.224671
|View full text |Cite
|
Sign up to set email alerts
|

Determination of composition of fatty acids in Saponaria officinalis L.

Abstract: Treatment using medicinal plants with a long history of use is of interest to our society. These plants include Saponaria officinalis L., as well commonly known as common soapwort belongs to the family Caryophyllaceae. The herb and roots of this plant used as a blood purifier, an expectorant in bronchitis, diaphoretic and diuretic, for skin diseases, to increase bile flow. The plant contains various secondary metabolites, but there is no information on the fatty acids composition of Saponaria officinalis L. her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Values were determined using Statistica v 10.0 (StatSoft Inc.) program. The level of significance was set at *p<0.05 for all statistical analyses [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Values were determined using Statistica v 10.0 (StatSoft Inc.) program. The level of significance was set at *p<0.05 for all statistical analyses [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…The performance parameters of the reference amino acid method, concentrations, limit of detection (LOD), limit of quantification (LOQ) and calibration curves were statistically calculated using Statistica v 10.0 (StatSoft I nc.) program (Budniak et al 2021b) and are shown in Table 1. All statistical tests were performed at a confidence level of 95% and k = 2.…”
Section: Validation Of the Methodsmentioning
confidence: 99%
“…To understand the mechanism of action of lyophilized DBH powder on glucose levels, it is necessary to further study the effect of this APhI on hydrocarbon metabolism. From the analyzed scientific literature, it can be assumed that the glycemia of the lyophilized powder of drone homogenate can be influenced by the flavonoids present in it by inhibiting the absorption of glucose in the intestine or by influencing its absorption by peripheral tissues (Pavliuk et al 2020;Stechyshyn et al 2020;Budniak et al 2021). Flavonoids are known to accelerate the use of glucose in the liver and skeletal muscle cells by activating key glycolysis enzymes hexokinase and pyruvate kinase, reduce glycogen phosphorylase activity and stimulate glycogen production in the liver and skeletal muscle cells (Pavliuk et al 2020;Shanaida et al 2020;Stechyshyn et al 2020).…”
Section: Secretionmentioning
confidence: 99%